Perception of undergraduate students in health area about emergency remote education in Brazil - Menech, Larissa Villwock de (2022)
Brazilian education faced numerous challenges with the emergence and spread of the coronavirus, so the work proposed to question undergraduates about the experience of emergency remote teaching and what were the facilities and difficulties encountered in the period. This is a mixed research: cross-sectional observational and descriptive qualitative. The population consisted of undergraduates in the area of ​​health from Brazilian state universities who answered the questionnaire via the Google Forms® on-line platform regarding emergency remote teaching during the Covid-19 pandemic, from September to November 2021. Descriptive statistics were performed for quantitative data, while for open questions the answers were categorized according to the discourse content analysis. Data from 67 undergraduates were analyzed, of which 56.7% reported having a good use of activities carried out on-line. 74.6% of students are satisfied with the adaptation of digital tools to monitor remote activities. In addition, 65.7% of undergraduates say that teachers performed well in adapting face-to-face content to remote content, highlighting its importance in the learning process. On the other hand, when asked about the facilities and difficulties they experienced in remote teaching, most reported negative aspects, such as concentration/learning difficulties, health problems, poor internet, inadequate environment, even didactic issues, such as the methodology adopted, the lack of interaction, difficulty in adapting the tools, in addition to the overload of activities.